2013
DOI: 10.1590/s1415-790x2013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Agregação de fatores de risco para doenças e agravos crônicos não transmissíveis em adultos de Florianópolis, SC

Abstract: Objective: To investigate clustering patterns of health risk behaviors for non communicable diseases and its associated factors. Methods: a Random telephone survey with 1,996 adults from Florianopolis, SC, was conducted in 2005. Tobacco use, high alcoholic intake episodes, fruit consumption and physical inactivity were investigated. Clustering was examined by the ratio between observed and expected prevalence of each of the 16 possible combinations. These clustered risk factors comprised the main outcome and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
3
13
0
8
Order By: Relevance
“…It may also reach 70% in rural Asian populations ( 27 ). Prevalence of clustering in Florianopolis was 43% in men and 37% in women ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may also reach 70% in rural Asian populations ( 27 ). Prevalence of clustering in Florianopolis was 43% in men and 37% in women ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a high prevalence of hypertension (20.3%), abdominal obesity (30.0%), hyperglycaemia (14.4%) and dyslipidaemia (65.0%) found among Brazilian adolescents [ 4 ], and the risk of these diseases could be reduced by acting on modifiable risk factors for NCDs (such as physical inactivity, excessive alcohol consumption, smoking, sedentary behaviour and unhealthy diet). Behavioural factors are more sensitive to interventions than clinical factors [ 5 ]. Moreover, habits acquired at this stage of life tend to persist in adulthood [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these risk factors for NCDs has a different impact on health. Adolescents with low levels of physical activity have a higher risk of hypertension [ 3 , 5 ]. Sedentary adolescents have a higher risk of obesity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies 44,48 with the adult population of Florianópolis found that men were two and ten times more likely to simultaneously have three or four risk behaviors for NCDs than women, respectively. The same studies corroborate the present research in relation to education, which showed that less educated participants aggregated and accumulated more risk behaviors.…”
Section: Discussionmentioning
confidence: 60%